REPRESENTATION OF CAPITALISM AND MATERIALISM IN JESSIE J’S PRICE TAG: A MARXIST PERSPECTIVE - Silvia Fara Diba Siregar; Rahma Amalia; Elva Gracia Sidabutar; Erluna Elekta Rajagukguk; T.Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This research seeks to examine how capitalism and materialism are represented in thelyrics of Jessie J’s song Price Tag from a Marxist point of view. The study centers on theportrayal of money domination as a manifestation of capitalist practice and onmaterialism as an element of commodification in contemporary society. The researchapplies a qualitative method using a descriptive-interpretative approach. The dataconsist of words, phrases, and sentences taken from the lyrics of Price Tag and areinterpreted through Marxist literary criticism. Data were collected throughdocumentation and library research, while the analysis followed the Miles, Huberman,and Saldana model, covering data condensation, data presentation, and conclusiondrawing. The findings indicate that Price Tag expresses criticism of the power of moneyand the culture of materialism within capitalist society. The lyrics illustrate howcapitalism forms social consciousness, causing money and consumption to becomedominant standards for measuring happiness and social status. The song also revealscommodification, a process that changes social relationships into economic relationsgrounded in exchange value. Through comparison, this research shows that Price Tagdiffers from many contemporary popular songs that tend to glorify luxury andmaterialistic lifestyles. Through cause-and-effect analysis, the study also demonstratesthat capitalism encourages consumerist habits, artificial needs, and social alienation.Therefore, this study confirms that song lyrics can operate as a medium of social criticismagainst capitalist ideology in modern popular culture.Keywords: Capitalism; Materialism; Marxism; Song lyrics; Social criticism